Alcohol use disorders are associated with higher healthcare expenditure among older adults with suspected cognitive impairment: A registry-based cross-sectional study - Ben Kamsvaag; Sverre Bergh; Jūratė Šaltytė Benth; Richard C. Oude Voshaar; Kjerstin Tevik; Geir Selbaek; Anne-Sofie Helvik (PLoS ONE, 2026)
Background High levels of alcohol consumption and cognitive impairment both drain our healthcare budget, but it is unknown whether alcohol use disorders (AUDs) influence healthcare costs among people with suspected cognitive impairment specifically. Methods This study aims to examine the association between alcohol-related ICD-10 diagnoses and healthcare costs among 2,736 Norwegians aged ≥60 years being assessed for cognitive impairment in Norwegian specialist healthcare and included in the Norwegian Registry of Persons Assessed for Cognitive Symptoms (NorCog). Linear regression analysis was applied to assess the relationship between ICD-10 alcohol-related diagnoses and the primary outcome variable: healthcare costs. Healthcare costs one year before and one year after clinical assessment were used to account for the expected shift in healthcare use after assessment. Results Median costs of healthcare use were €2,226 (Q1-Q3 1,076−4,107) one year before assessment and €2,217 (Q1-Q3 1,160−4,006) after. One year prior to NorCog assessment, participants with AUDs had approximately 50% higher costs compared to participants without an AUD (median of €3,286 and €2,190, respectively). One year after NorCog assessment, this difference was negligible. An interaction between AUD status and time was significant, implying that post-diagnostic care for cognitive impairment may simultaneously mitigate the healthcare burden associated with AUDs or its related sequelae. Conclusion Our findings indicate that alcohol consumption is a potentially important and amenable determinant of healthcare use, knowledge which could be valuable in planning treatment and care. Such knowledge could also possibly curtail the higher healthcare costs among older adults with AUDs. Thus, we urge healthcare providers to routinely ask patients about their alcohol consumption.